Vitamin E production in Amaranthus sp. and Allium porrum by co-suppression of homogentisate phytyltrransferase and tocopherol cyclase genes from Elaeis guineensis - Munusamy, Umaiyal (2013)
Vitamin E is a fat-soluble vitamin that consists of four different tocopherol and tocotrienol isomers (α, β, γ and δ). Medical evidence suggests that vitamin E especially α-tocotrienol protects the cells against cancer, is a strong antioxidant and an effective neuroprotector. However, α-tocotrienol can only be found in seeds/cereal grain. In this study α-tocotrienol was produced by co-suppression of α-tocopherol by silencing the expression of two key vitamin E biosynthetic genes, homogentisate phytyltransferase (HPT) and tocopherol cyclase (TC) in Amaranthus sp. and Allium porrum leaves by transient transformation. HPT catalyses the condensation of homogentisate (HGA) and phytyl diphosphate (PDP). While TC forms the chromanol headgroup of the various tocopherol isomers. Gene silencing was performed using short sense conserved gene sequences of HPT and TC isolated from Elaeis guineensis. Through bioinformatics analysis, both isolated HPT and TC cDNAs were successfully verified to possess similar characteristics of the HPT and TC from other plant species. These isolated genes were predicted to encode a protein of 151 and 207 amino acid residues and they fell under the UbiA superfamily and tocopherol_cyc1 superfamily, respectively. Five gene constructs were generated p5b5, p5d9, p5f7, p4a11 and p4c9 driven either by the maize ubiquitin promoter (Ubi1P) or the Elaeis guineensis leaf-specific promoter (LHCB), in pDRB6b expression vector. All five recombinant vector constructs were successfully cloned, giving the expected size bands in gel electrophoresis analysis. The PCR product of the recombinant vector shared 78% identity with HPT from Zea mays (NM001112407.1). While the TC cDNA showed 79% identity with Vitis vinifera (XM002281388.2). In addition, plasmid stability in the transformed AGL1 showed stability ranging from 40% to 60%, identical to pDRB6b vector in AGL1. Optimised HPLC analysis showed that α-tocopherol was suppressed with different trend among the constructs (from minimum 4% up to 100%) in all transiently transformed plants. The p5f7 construct (LHCB-Ubi1intron-HPT-NosT) worked best in Allium porrum to suppress α-tocopherol in the range 62%-86%. While, p4c9 construct (LHCBTC-NosT) showed suppression up to 100% in Amaranthus sp. The results confirmed that the usage of LHCB showed better silencing than UbiP. In addition, with the usage of HPT gene, α-tocopherol was suppressed better (up to 86%) in Allium porrum than in Amaranthus sp. (75%). However, with TC gene the suppression was better in Amaranthus sp. (100%) than Allium porrum (57%). The production of α-tocotrienol was observed upon suppression of α-tocopherol using all recombinant vector constructs. With HPT gene the level of α-tocotrienol production was not dependent but with TC gene it was dependent on the level of α-tocopherol suppression. Overall, α-tocotrienol was produced more in Allium porrum than in Amaranthus sp. with p5d9 construct (Ubi1P-Ubi1intron-HPT-NosT). Thus, Amaranthus sp. and Allium porrum which do not accumulate α-tocotrienol naturally had shown to produce α-tocotrienol after suppression in the α-tocopherol production through transgenic manipulation. Finally, Agrobacterium -mediated transformation of inflorescence of Amaranthus sp. was carried out through drop by drop technique for producing transformed seeds. Nineteen transgenic plants were successfully obtained with transformation efficiency from 0.1% up to 2% for each constructs. This could serve as a potential system to engineer production of α-tocotrienol in transgenic Amaranthus sp.